The analysis of translation in short story of Jim Anderson â€œThe Ladybug Prayerâ€ based on social, culture and information studies - Sylvana, Tsani; Riady, Yasir (LADU: Journal of Languages and Education, 2021)
Background: Â It is always attracted in choosing short story entitled â€œ A Ladybug prayerâ€, since the feels and story which really interesting and appreciate with structure of words, the sentence in English and limit from point of view in translator and translation, and how to find a good equality of meaning from the beginning in English into Indonesian. The Ladybug Prayer communicates a story around a boy who will â€œsavedâ€ in church. In spite of, he donâ€™t identify or really know that he will saved from something, and finally, he knows about saved, through the ladybug prayer. This story, however based on true story. Sometimes you must be cautious and watch with what you pray of.Purpose: It is really interested to translate this story since the writer want to identify problems which are found in translating in the Ladybug prayer with the Indonesian version.Design and methods: The writer used the library in this research with reference to find and look for books that have relative and connection in translation and its connection in social, culture and information studies.Results: The short story entitled â€œA Ladybug prayerâ€ has a very beautiful story with simple and complicated words.